Near-Infrared Optoelectronic Non-Invasive Sensing Technology for Glucose Concentration Monitoring in Liquid Solutions - Sahakyan, M.; Manukyan, G.; Gambaryan, K.
The accurate and non-invasive monitoring of glucose concentration in aqueous solutions is crucial for various biomedical and industrial applications. Despite advancements, traditional glucose measurement methods remain invasive and require frequent sample collection. This study presents an innovative approach using a near-infrared optoelectronic system to measure glucose concentration in pure water. By exploiting specific absorption wavelengths of glucose (1.5 and 1.9 μm), a reliable, non-invasive detection method is developed. The study involves spectral analysis, experimental validation using glucose solutions of varying concentrations, and the development of a prototype. The proposed system offers a promising solution for precise, real-time glucose monitoring, overcoming the limitations of traditional methods.
Keywords: Physics